Implementing Educational Language Policy in Arizona Legal, Historical and Current Practices in SEI - Arias, M. Beatriz; Faltis, Christian (Multilingual Matters, 2012)
This volume is a unique contribution to the study of language policy and education for English Learners because it focuses on the decade long implementation of "English Only" in Arizona. How this policy influences teacher preparation and classroom practice is the central topic of this volume. Scholars and researchers present their latest findings and concerns regarding the impact that a restrictive language policy has on critical areas for English Learners and diverse students. If a student's language is sanctioned, do they feel welcome in the classroom? If teachers are only taught about subtractive language policy, will they be able to be tolerant of linguistic diversity in their classrooms? The implications of the chapters suggest that Arizona's version of Structured English Immersion may actually limit English Learners' access to English
Description based on online resource; title from PDF title page (publisher's Web site, viewed 25. Jul 2018)
Keywords: language education; language policy; monolingualism; Structured English Immersion; Education, Bilingual -- Arizona; English language -- Study and teaching -- Immersion method; English language -- Study and teaching -- Arizona -- Foreign speakers; Language policy -- Arizona